Marinasi Berbagai Jenis Alkohol terhadap Kadar Air, Oksidasi Lemak, dan TPC Na’an Maran - Ferdi Alosius Fina; Gemini E. M. Malelak; Heri Armadianto (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to determine the effect of administering various types of alcoholic beverages (beer, red wine, and Sophia) on the moisture content of na'an maran, the comparison of moisture content between raw meat and na'an maran, fat oxidation, and total plate count (TPC). The method used was a completely randomized design (CRD) consisting of 4 treatments and 4 replicates, resulting in 16 experimental units. The administration of several types of alcoholic beverages consisted of P0 = control, P1 = 10% beer, P2 = 10% red wine, and P3 = 10% Sophia. The parameters measured in this study were the moisture content of raw meat, the moisture content of na'an maran, fat oxidation, and the total plate count (TPC) of na'an maran. The results showed that the addition of various types of alcoholic beverages had a significant effect (P˂0.05) on the moisture content of raw meat and fat oxidation, and had no significant effect (P> 0.05) on the moisture content of na'an maran and TPC. The lowest moisture content was found in P3 = 26±2.67 and the highest in P0 = 31.7±3.58. The lowest fat oxidation of na'an maran was found in P0 = 1.2±0.06 and the highest in P3 = 1.94±0.05. The conclusion is that the use of wine alcohol and Sophia causes higher fat oxidation compared to the control. Meanwhile, moisture content and TPC did not differ.